2017
DOI: 10.1002/jcc.24876
|View full text |Cite
|
Sign up to set email alerts
|

A new nonempirical tuning scheme with single self‐consistent field calculation: Comparison with global and IP‐tuned range‐separated functional

Abstract: System-dependent nonempirical tuning of range-separated functional provides a way to minimize the delocalization error of the system. However, existing nonempirical tuning method requires the computation of several ΔSCF calculations to determine the optimal μ value. In this article, we have defined a scheme to evaluate the optimal μ value with single self-consistent field calculation. Our method is based on the evaluation of the spherically symmetric average Electron localization function (ELF) region. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…Although the amount of HF exchange can be expressed as a function of an inherent molecular property, i.e., the LOL domain, the problem of how to directly gauge the explicit amount of HF exchange remains unsolved. Recently, ω* was reported to follow a quasilinear relationship with the mean ELF distance . Because of the similarity between the ELF and LOL, the following relationship can be adapted where C 1 and C 2 are the numerical constants (0.588 and 0.115, respectively) determined by the minimization of the calculated E VA (S 1 ) of 10 typical TADF training molecules (Table S1) using the experimental data of E VA (S 1 ) in cyclohexane as references (Figure d) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the amount of HF exchange can be expressed as a function of an inherent molecular property, i.e., the LOL domain, the problem of how to directly gauge the explicit amount of HF exchange remains unsolved. Recently, ω* was reported to follow a quasilinear relationship with the mean ELF distance . Because of the similarity between the ELF and LOL, the following relationship can be adapted where C 1 and C 2 are the numerical constants (0.588 and 0.115, respectively) determined by the minimization of the calculated E VA (S 1 ) of 10 typical TADF training molecules (Table S1) using the experimental data of E VA (S 1 ) in cyclohexane as references (Figure d) .…”
Section: Resultsmentioning
confidence: 99%
“…Intuitive wave function analysis tools, for example, the electron localization function (ELF) and localized orbital locator (LOL), can be used to reveal qualitative chemical information, including atomic shells, covalent bonds, and noncovalent interactions. , It is reported that noncovalent interactions between the metal cations and protein can be intuitively shown with different strength to explore the selectivity using the ELF tool . Therefore, these kinetic-density-based tools can identify the localization and delocalization regions in a molecule and thus can be used to construct the descriptor for determining the ω*. , It has been reported that the nonempirical ELF-tuned RS functional can reliably reproduce the vertical IPs of various small organic molecules and achieve precision approaching that of the coupled cluster single, double, and perturbative triple (CCSD­(T)) method . Since only one single-point calculation is required to obtain the kinetic density in the tuning procedure, we can establish efficient LOL-tuning methodology for large-size TADF molecules in the gas phase and the solvation process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the longrange corrected models considered herein, there are also other types of range-separation schemes where either the percentage of HF exchange can decrease from SR to LR so that it vanishes at LR part (known as screened-exchange hybrids) [86][87][88][89] or increase from SR to a maximum value at medium range and then decreases to zero at LR limit. 90,91 Plus, apart from the optimal tuning procedure employed in this work, there are also other tuning schemes to determine the optimal value of the range-separation parameter, such as those previously used by others [92][93][94] and ours. 95 Our study can hopefully function as an inspiring avenue towards continued progress using such frameworks in the field of electrically pumped OSLDs, whose results may be reported elsewhere in a comparative investigation.…”
Section: Resultsmentioning
confidence: 99%
“…This improves properties based on orbital energies, such as vertical ionization energy (IE), electron affinity (EA), fundamental gap (FG), optical gap, charge-transfer excitation as well as Rydberg excitation [33,34]. Besides the traditional γ-tuning scheme based on satisfying Koopmans' theorem, recent advances based on electron localization function and localized orbital locator have been developed in the literature which requires only one single self-consistent field calculation [35,36]. Moreover, a self-consistent OT-RSH approach [37] has been developed based on the minimization of inter-atomic forces, which offers better geometries and vibrational modes.…”
Section: Introductionmentioning
confidence: 99%